Pseudomonas aeruginosa bacteraemia in two UK district hospitals - David A. Enoch; Julie Kuzhively; Andrew Sismey; Alina Grynik; Johannis Andreas Karas (MDPI AG, 2013)
Pseudomonas aeruginosa bacteraemia is associated with significant morbidity and mortality. We retrospectively studied the epidemiology of bacteraemia due to P. aeruginosa in two UK district hospitals so as to determine prevention strategies and assess the efficacy and compliance with local hospital antibiotic guidelines. Eighty six episodes occurred in 85 patients over the 3 year period. There was a year on year increase in bacteraemias, due predominantly to an increased proportion of community-onset episodes. Urinary catheterisation was a significant risk factor, along with anaemia, renal disease, malignancy and diabetes. The antibiotic guidelines were adequate for 92.8% of episodes but only 73.8% of patients received adequate therapy. Failure to follow the guidelines was principally due to unwillingness to use gentamicin due to concerns about nephrotoxicity. The antibiotic guidelines may need reviewing to accommodate this problem and further work is required to address urinary catheter care in both the hospital and community. Pseudomonas aeruginosa should be considered a significant pathogen when patients are admitted with features of sepsis.